The Many faces of Legal Positivism - Redondo, Maria Cristina (2015)
This paper provides a discussion on legal positivism and can be ideally divided into two main parts. The first one deals with Norberto Bobbio´s distinction of three kinds of legal positivism: methodological, theoretical and ethical positivism. In this regard, the paper articulates some considerations aiming to show that, as far as it is not possible to identify what are the theses on which each one of these three kinds of legal positivism converges, the proposed classification does not seem justified. The second part of the paper is devoted to showing that, at any rate, the distinction indicated by Bobbio is still highly relevant in order to identify the different kinds of theses that characterize legal positivism as a single position. As a matter of fact, there exist different conceptions of legal positivism, which are the expression of a deep disagreement about what methodological, theoretical and ideological theses define legal positivism. In this regard, it is argued that there are at least three theses which every legal positivist is committed to accepting. Such theses do not constitute a set of necessary and sufficient conditions governing the use of the expression "legal positivism". However they make it possible to offer an analysis of the necessary properties that define a paradigmatic example of legal positivism.